2014
DOI: 10.1002/adfm.201303879
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Bi2S3Nanocrystals: Quantum Size Effects and Midgap States

Abstract: Among solution-processed nanocrystals containing environmentally benign elements, bismuth sulfi de (Bi 2 S 3 ) is a very promising n-type semiconductor for solar energy conversion. Despite the prompt success in the fabrication of optoelectronic devices deploying Bi 2 S 3 nanocrystals, the limited understanding of electronic properties represents a hurdle for further materials developments. Here, two key materials science issues for light-energy conversion are addressed: bandgap tunability via the quantum size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 60 publications
(91 reference statements)
3
44
0
Order By: Relevance
“…An overall trap density of the order of 10 20 cm À3 was assigned to the contribution of surface states caused by incomplete surface passivation. 35 From our data, the calculated trap concentration is of the order of 10 16 cm À3 . Thus, it can be concluded that the determined trap concentration at temperatures below 160 K could originate from the nanowire bulk.…”
Section: Resultsmentioning
confidence: 90%
“…An overall trap density of the order of 10 20 cm À3 was assigned to the contribution of surface states caused by incomplete surface passivation. 35 From our data, the calculated trap concentration is of the order of 10 16 cm À3 . Thus, it can be concluded that the determined trap concentration at temperatures below 160 K could originate from the nanowire bulk.…”
Section: Resultsmentioning
confidence: 90%
“…source (Quantronix Integra series), delivering 130-fs-long pulses in KHz repetition rate trains, 1 mJ energy per pulse 57 . Samples were kept in vacuum and the optical emission was dispersed by a spectrometer (Acton 2300 series with a 50 g mm À 1 , 600 nm blaze grating) coupled to a streak camera (Hamamatsu C5640).…”
Section: Methodsmentioning
confidence: 99%
“…However, for some applications such as photocatalytic water splitting, this narrow E g is not sufficiently large to drive the uphill reactions with theoretical energy requirements >1.23 eV plus the known overpotentials (Supporting Information, Figure S8). Our PILs‐controlled Bi 2 S 3 crystals show a striking increase of the E g (Figure ), presumably due to the quantum size effects arising from a reduction of the crystal size . An ultraviolet–visible (UV/Vis) spectrum (Figure ) reveals that the Bi 2 S 3 nanowires show an intrinsic semiconductor‐like absorption in the red region of the visible spectrum with an E g of 1.95 eV (Supporting Information, Figure S9).…”
Section: Figurementioning
confidence: 99%